Cognition and strategy - Gavetti, Giovanni; Ocasio, William (Advances in strategic management ;, 2015)
The "cognitive foundations" of strategy have received increased attention in recent years. The last decade has witnessed a dramatic rise in empirical studies that seek to document the role of cognition in strategic outcomes, and in theoretical work that seeks to systematize this relationship. Drawing on psychological foundations in general, and on cognitive representation, framing, and categories in particular, this research has made significant progress, yet remains in a preparadigmatic phase where polysemy and terminological variety are still the norm. This volume has two goals. First, it intends to attract a representative sample of the most significant empirical and theoretical developments in the field of cognition and strategy. Second, it intends to take stock of these developments by proposing a preliminary synthesis of the disparate advances in this field.